Albiglutide: A New GLP-1 Receptor Agonist for the Treatment of Type 2 Diabetes. (November 2014) - Trujillo, Jennifer M.; Nuffer, Wesley
Objective: To review the pharmacology, pharmacokinetics, safety, and efficacy of albiglutide, a glucagon-like peptide-1 receptor agonist (GLP-1 RA) in type 2 diabetes (T2D).Data Sources: A MEDLINE search (1950-June 2014) was conducted using the keyword albiglutide . References were reviewed to identify additional sources.Study Selection and Data Extraction: Articles evaluating pharmacokinetics, pharmacodynamics, safety, or efficacy of albiglutide were included.Data Synthesis: Albiglutide is a long-acting GLP-1 RA that lowers glycosylated hemoglobin (A1C) and reduces weight by stimulating glucose-dependent insulin secretion, suppressing glucagon secretion, delaying gastric emptying, and promoting satiety. Albiglutide has a long half-life as a result of resistance to degradation by dipeptidyl peptidase-4 and fusion to albumin, thus allowing once-weekly dosing. Albiglutide has been studied as monotherapy and add-on therapy to metformin, sulfonylureas, thiazolidinediones, insulin glargine, and varying combinations of these agents. Clinical studies have shown albiglutide to be superior to placebo, sitagliptin, and glimepiride and noninferior to insulin glargine and insulin lispro at reducing A1C in T2D patients, with A1C changes from baseline ranging from −0.55% to −0.9%. Noninferiority was not achieved when compared to liraglutide and pioglitazone. Weight changes ranged from +0.28 to −1.21 kg. The most common side effects are upper-respiratory-tract infections, diarrhea, nausea, and injection-site reactions.Conclusion: Albiglutide is the fourth GLP-1 RA approved in the United States. Advantages include once-weekly dosing and fewer gastrointestinal side effects compared with liraglutide, but it is less effective at reducing A1C and weight compared to liraglutide. It has not been compared head to head with other GLP-1 RAs.